THE INFLUENCE OF QUALITY TOURIST OBJECT AND EFFECTIVENESS OF PROMOTION TOWARD TOURIST’SLOYALTY OF GEDONG SONGO TEMPLE AT CENTRAL OF JAVA - Winarto, Winarto (Admisi dan Bisnis, 2017)
GedongSongo Temple is a culture heritage was developed as superior culture and mountainous landscape tourist object by Semarang regency government. Gedong Songo Temple complex are eight Hindu buildings temple at fresh and beautiful landscape of mountain slopeUngaran. Semarang regency government developed several facilities Gedong Songo Temple tourist object and promotion activities to build tourists loyalty. Purposes of this research are: the fist to measure of quality Gedong Songo Temple tourist object, effectiveness of promotion and to tourist’s loyalty. Secondly to analyse ofinfluencing of quality GedongSongo Temple tourist object and effectiveness of promotion toward tourist’s loyalty. Questionnaire used to collect data, size of sample are 100 respondents. Results of this research are: degree of overall quality Gedong Songo Temple tourist object is quite satisfied; degree of overall effectiveness of promotion is quite effective and degree of overall tourist loyalty of Gedong Songo Temple object tourist is fair to. The quality Gedong Songo Temple tourist object has positive influence toward tourists’ loyalty. Likewise, effectiveness of promotion has positive influence toward tourist’s loyalty.